Lateral Decubitus Positioning For Shoulder Arthroscopy - Anjay K. Batra BS; Christopher M. Brusalis MD; Harkirat Jawanda BS; Garrett Jackson MD; Nikhil N. Verma MD (SAGE Publishing, 2023)
Background: Lateral decubitus positioning is a frequently employed technique to perform shoulder arthroscopy. Proper patient positioning and equipment setup is crucial to ensure a safe and efficient surgery. Indications: The common indications for performing a shoulder arthroscopy in the lateral decubitus position include anterior shoulder stabilization, posterior shoulder stabilization, superior labrum anterior to posterior (SLAP) repair, diagnostic arthroscopy for internal impingement, and arthroscopic capsular release for adhesive capsulitis. Technique Description: After undergoing general endotracheal anesthesia in the supine position on a standard operating room table, the patient is rotated into the lateral decubitus position with the operative arm facing upward. The patient's head is supported with a pillow to ensure a neutral position. The nonoperative arm is flexed forward and rests on a padded arm board. The sides of a bean bag are applied to the patient's torso to maintain the lateral decubitus position, and the bean bag is deflated to remain rigid. An axillary roll is placed under the axilla, and foam pads are placed below the "down leg" and between both legs. A commercial arm jack is positioned on the anterior, proximal side of the operating room table to allow for 20° of shoulder abduction, which maximizes the glenohumeral joint space. Results: Advantages of the lateral decubitus position over the beach chair position include improved access to the anterior, inferior, and posterior glenoid; more ergonomic positioning for the operating surgeon; lower risk for patient cerebral hypoperfusion; and reduced rates of recurrent instability following arthroscopic stabilization in comparison to procedures performed in the beach chair position. Disadvantages of the lateral decubitus position include risk of traction-related neurovascular injury, requirement of an arm suspension device, and increased difficulty in rotating the shoulder intraoperatively. Discussion/Conclusion: Lateral decubitus positioning is commonly used to achieve a circumferential view of the glenohumeral joint in shoulder arthroscopy. This surgical position yields several advantages for the operating surgeon and has been shown to be associated with improved clinical outcomes after shoulder instability surgery. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.